The toponymy of communal activity: Anglo-Saxon assembly sites and their functions - Baker, John (ICOS, 2014)
The paper builds on earlier discussion of the multiple functions of medieval judicial assembly sites, providing a comprehensive evaluation of relevant English hundred-names, and making reference to associated microtoponymy. While religious, military, commercial, and recreational activities may all have occurred at assembly-sites, it can be hard to delineate the evidence so clearly along these lines, and attempts to do so may be anachronistic in some instances; nevertheless, the analysis of different group activities has important implications for our understanding of the evolution of the hundredal system and its impact on society at large.